2015
DOI: 10.1117/12.2183286
|View full text |Cite
|
Sign up to set email alerts
|

Third Harmonic Generation microscopy as a diagnostic tool for the investigation of microglia BV-2 and breast cancer cells activation

Abstract: Nonlinear optical imaging techniques have created new opportunities of research in the biomedical field.Specifically, Third Harmonic Generation (THG) seems to be a suitable noninvasive imaging tool for the delineation and quantification of biological structures at the microscopic level. The aim of this study was to extract information as to the activation state of different cell types by using the THG imaging microscopy as a diagnostic tool.BV-2 microglia cell line was used as a representative biological model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…THG advantage is that the main signal is generated within intact live cells and tissues, when there is a change in the refractive index or change of the third order susceptibility values, without the need of any staining . Previous studies have shown that lipid bodies are the main intracellular sources for the high THG signals , while others have indicated that polarized THG microscopy can discriminate triacylglycerols from cholesteryl esters in intact mammalian cells .…”
Section: Introductionmentioning
confidence: 99%
“…THG advantage is that the main signal is generated within intact live cells and tissues, when there is a change in the refractive index or change of the third order susceptibility values, without the need of any staining . Previous studies have shown that lipid bodies are the main intracellular sources for the high THG signals , while others have indicated that polarized THG microscopy can discriminate triacylglycerols from cholesteryl esters in intact mammalian cells .…”
Section: Introductionmentioning
confidence: 99%
“…This paper introduces backward THG imaging microscopy to image unstained healthy and malignant breast biopsy tissue. Previously THG microscopy has been used to study the resting and activated states of microglial cells present in breast tissue (Gavgiotaki et al ., ). However, to the best of our knowledge, the work in this paper will be the first application of THG imaging on unstained breast tissue biopsies.…”
Section: Introductionmentioning
confidence: 97%
“…Using the spectral information cancerous breast tissue can be distinguished from normal and benign tissue, both ex‐vivo and in‐vivo . Studies using SHG/THG microscopy to image breast tissue have also shown very promising results, but were applied on stained and fixated breast tissue , unstained but fixated breast biopsies or breast cell lines . Tu et al applied label‐free multimodal multi‐photon microscopy (including SHG/THG microscopy) to unprocessed breast tissue to visualize the micro‐environment of mammary tumors induced in rats, and to visualize extra‐cellular vesicles in the stroma tissue of a human tumor specimen.…”
Section: Introductionmentioning
confidence: 99%